SOIL DENSITY IMPACT ON SOIL-WATER CHARACTERISTIC CURVE AND PORE-SIZE DISTRIBUTION - Pernebekova, Gulnur (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The mechanical and hydraulic characteristics of unsaturated soil mechanics are defined by the soil-water characteristic curve (SWCC). The pore structure, mineral varieties, and physical features of a soil sample all have a significant impact on the parameters and shape of the SWCC. This research examined how varying percentages of water content are affected by soil density in relation to suction by means of SWCC and variance in porosity from pore-size distributions (PSD) of unsaturated soil. Two different soil types engineered soil samples from Astana, Kazakhstan and different sand-kaolin mixtures, purchased from manufacturer were tested in this study. Tested samples were compacted at optimum water content (OWC), wet of optimum and dry of optimum. SWCCs were generated using Tempe cell with suction range from 0 to 100 kPa and WP4C with suction range from 0 to 300 MPa. The PSDs were estimated using the differentiated equation of Fredlund and Xing (1994) and examined using the Scanning electron microscope (SEM) analysis. The mineral composition of soil samples was defined using the X-ray diffraction (XRD) analysis. The SWCC testing results indicated that sample compacted at OWC and dry of optimum likely to have bimodal SWCC, while sample compacted wet of optimum likely to have unimodal SWCC. Dry density of soil increased as the AEV decreased. In addition, this resulted in decreasing water content. Dominant pore sizes with maximum frequency increased with the decreasing dry density of soil, which resulted in increased matric suction. The soil samples of SWCC lied in the range of created envelope to evaluate the obtained results. However, the PSD values including maximum pore size and frequency didn’t fit well the given range. In summary, the laboratory findings may be applied practically and are able to represent the hydraulic behavior of tested samples.
Keywords: soil-water characteristic curve; pore-size distribution; unsaturated soil; soil density; moisture content; type of access: embargo